Yield and yield attributes of rabi sunflower (Helianthus annuus L.) As influenced by sowing dates and irrigation levels - A. MANI, G.G.R. MUKHESH, G. MANOJ KUMAR., K. AVILKUMAR and (The Journal of Research, PJTSAU, 2017)
Sunflower (Hellianthus annuus L.) seed is an important oilseed contain good quality oil (34-52%) as well as high amount of protein (14%) as reported by Singh et al. (1997). Sowing times play a major role in effecting the growth and yield of sunflower. Varied sowing dates and varied rainfall at different growth stages effect the availability of water. Numerous research studies for different climates have shown that sowing date influences the growth, seed yield and quality. The best irrigation regime can not only saves the water and also regulates the impact of erratic rainfall and conserve moisture. Hence, an attempt was made to study the best sowing date and irrigation regime of sunflower in Rajendranagar, Hyderabad, climatic conditions.